Corpos e sexualidades que transgridem: análise comparativa e gendrada dos Poemas de Bufólicas, de Hilda Hilst - Cavalcante, Nathalie Sá (2015)
This work, which is divided in three chapters, is characterized by individual and comparative analyses of the poems presented in the work Bufólicas (1992), by brazilian contemporaneous writer Hilda Hilst. In the first chapter, we discuss theoretical issues that will guide these analyses, such as the relation between gender and literature, some considerations about contemporaneous and erotic literature, patriarchalism, symbolic violence, sexualities and identities. In the second chapter, Hilst’s life and work are depicted, as regards her appropriation of fairy tales, followed by the individual analysis of seven poems. In the last chapter, the poems are analysed under a comparative perspective, verifying the manner dialogs occur between the author and the illustrator, Jaguar, the portrayal of carnivalization, the subversion of gender roles, and body representation. The main theoretical basis used in this work derives from Arendt (1958), Bakhtin (1987), Bataille (1987), Beauvoir (1970), Bonnici (2007), Bourdieu (2001), Candido (2006), Culler (1999), Delphy (2009), Foucault (1976), Musskopf (2005), Saffioti (2009), Scott (1995) and Xavier (2007). As results, we certified that through the carnivalization and through bodies and sexualities that transgress, the author ridicules ideas derived from patriarchalism - such as sexism and repression of the feminine sexuality -, gives prominence to the symbolic violence suffered by the characters and discusses social issues related to identity and sexuality, as for instance, homophobia and biphobia. Finally, this presented work aims to incorporate close areas, or fields that meet each other, still, with an extensive academic dissemination: literary criticism based on gender studies and literary criticism on contemporaneous erotic poems written by women.